STRATEGI BELAJAR MATEMATIKA TUNANETRA X YANG BERPRESTASI TINGKAT NASIONAL (Penelitian Deskriptif Kualitatif di MAN 2 Payakumbuh) - SABRI - (Jurnal Penelitian Pendidikan Khusus, 2015)
This research was initiated by a student with visual impairment named X studying at MAN 2 Payakumbuh. X had totally visual impairment since he was born. Unfortunately, during his study, he was never accompanied by a Special Companion Teacher. In addition, none of the teachers teaching in the school had training on special education, so that the teachers did not know the strategies used to teach the students with visual impairment. Nevertheless, X was still able to gain a proud achievement. He won several competitions in Mathematics and went to national level.                This research used descriptive qualitative method. The data were collected through observation, interview and documentation study. The subject of the research was a student with visual impairment in class XII Agama 2.                The results of the research revealed that the ability of X during Mathematics learning process was very good. To learn, he maximized his auditory ability and he did not arrange special schedule for study. While studying in the classroom, there was no special service or certain media used to help X. He took note on important materials by using his own words. Furthermore, he had additional time to learn at school. At home, X reviewed the learning materials he had learnt by reading his note-book, listening to the recorded materials given by the teacher, listening to his friends reading the textbooks, and search for the materials in internet. In the examination, X did not take the exam together with his friends, instead, he took the test alone and listened to the teacher reading the test items. X would answer the questions by using Braille. Kata kunci: Tunanetra, Strategi Belajar, Prestasi